Make women artists visible. Design and application of an inclusive didactic unit on avant-garde basedon attitudinal contents and historical thinking - Zaragoza Vidal, María Victoria (Clio. History and History Teaching, 2019)
This study analyzes the results obtained after the implementation of a didactic unit on the artistic avant- garde in the subject of History of Art of the 2nd year of high school based on the historical thinking, the attitudinal contents and the visibility of the women artists. Later, the information gathered before and after the application of the didactic unit of innovation was analysed. The results obtained indicate that the students have developed a more complete vision of the artistic avant-garde, their context and the finality of the works, facilitating their understanding. In addition, this innovative methodology has allowed students to get to know another history of art, where women artists have their role, as well as working on procedural and attitudinal contents, to participate more in classes and to acquire second- order concepts.
Keywords: innovation; historical thinking; gender equality; didactic unity; avant-garde